CLIMATE CHANGE AND ITS EFFECTS ON OUR PLANET - Ibragimova Farida Ibodulloyevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation (English): This article discusses the problem of climate change and its impact on the planet. It highlights the main causes of climate change, such as human activities and industrial development, as well as its consequences, including global warming, rising sea levels, and damage to ecosystems. The article also emphasizes the importance of collective action and sustainable solutions to protect the environment for future generations.